Retaining Connectivity In Mobile Communication Mesh Networks. Issue 1 (July 2017) - Pisano, Alessandro; Franceschelli, Mauro; Pilloni, Alessandro; Shtessel, Yuri; Usai, Elio
Abstract: This paper deals with the problem of retaining the connectivity in a Mobile Ad-hoc communication mesh Network (MANET). A multi-agent systems perspective is taken, where primary mobile agents (PAs) can only communicate when the relative distance is less than a "visibility range". PAs form a network that can become disconnected depending on how they move to achieve their global task (which does not include the connectivity maintenance). To retain connectivity, a number of Relay Agents (RAs), whose motion is governed by a command center (CC), are sent to the field to act as "communication bridges" enforcing the global connectivity of the network containing both the PAs and the RAs. Graph-oriented concepts and analysis tools, particularly the minimal spanning tree (MST) notion, are adopted in the present work to analyze the connectivity properties of the network and to establish in real time how many additional RAs are required and how they should move in order to prevent the connectivity loss. Artificial potential fields and finite-time control techniques are utilized to drive the relay agents to their waypoints while avoiding the collisions. Numerical examples confirm the efficacy of the proposed multi-layer control strategy.